PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 164 PEKANBARU - Irdiyawan, Tifani; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low learning outcomes of science subject "ilmu pengetahuan alam (IPA)” of students grade 5th of SD Negeri 164 Pekanbaru, with grade average 61.38, while the minimum exhaustiveness criteria "kriteria ketuntasan minimal (KKM)” for IPA is 75. Among 36 students, only 14 students who reached KKM with 38.88% classical completeness. This research is type of classroom action research "penelitian tindakan kelas" (PTK) which aimed to improve IPA learning outcomes of students grade 5th of SD Negeri 164 Pekanbaru, by implementing problem based learning model(PBL). Collection data conducted by observation sheet of teachers activity and students activity also the learning result. The average of IPA learning outcomes obtained by students before action is 61.38, increased to 74.30 in the first cycle with the percentage increase of 21.04%. In the second cycle increased to 81.23 with a percentage increase of 32.33%. Teacher activity in the first cycle of the first meeting obtained a score of 13 (65%) with sufficient category and at the second meeting obtained a score of 16 (80%) with a good category. On the second cycle of the first meeting scores obtained are 17 (85%) with a good category and the second meeting obtained a score of 18 (90%) with a very good category. Student activity on the first cycle of first meeting had got score 13 (65%) with enough category and at the second meeting had got score 16 (80%) with a good category. In the second cycle of the first meeting scores obtained 17 (85%) with a good category and the second meeting scored 19 (95%) with a very good category. The result of research in 5th grader class of SD Negeri 164 Pekanbaru proves that implementing problem based learning model can improve student learning result of IPA subject.Keywords: Problem Based Learning, IPA Learning Result